Stability and Evolution of Preferences for Improved Cookstoves : A Difference-in-Difference Analysis of a Choice Experiment from Ethiopia - Dissanayake, Sahan T. M.; Voigt, George; Cooper, Abbie; Beyene, Abebe Damte; Bluffstone, Randall; Gebreegziabher, Zenebe; LaFave, Daniel; Martinsson, Peter; Mekonnen, Alemu; Toman, Michael (World Bank, Washington, DC, 2019)
There is a growing effort in the non-market valuation literature toward better understanding of the stability and evolution of preferences over time. The study uses a novel approach combining a repeated choice experiment with a randomized controlled trial on stove adoption in Ethiopia to analyze the stability and evolution of preferences. The treatment group in the randomized controlled trial received an improved fuelwood stove with less fuelwood use, whereas the control group continued to use traditional cooking methods. Respondents were given the exact same choice questions in 2013 and 2016. The study began with 504 households in 36 communities in 2013, and 486 of the same households participated in 2016 (a 96 percent retention rate). The results show that preferences of the respondents from the control group are stable over the study period, while preferences of the respondents from the treatment group evolve. Moreover, households in the treatment group still using the stoves have significantly higher willingness to pay for all the stove's attributes in 2016 compared with 2013, indicating how longer experience can increase the willingness to pay for technology with environmentally preferable attributes.